Heart rate variability in orthostatic test during different training periods in elite swimmerns - Hynynen, E.; Iglesias, X.; Feriche, B.; Calderon, C.; Abalos, X.; Vazquez, J.; Barrero, A.; Rodriguez, L.; Levine, B. D.; Rodriguez, F. (Sport Science Research Group, INEFC-Barcelona, 2012)
Intense training has been shown to change the autonomic modulation of the heart in endurance athletes assessed by heart rate variability (HRV) analysis. In overtraining state HRV diminished in athletes of different sports. PURPOSE: This study investigated the effects of intensified training and tapering on HRV in elite swimmers. METHODS: Eleven elite swimmers (7 F and 4 M, age 17.9 ± 1.9 y) lived and trained for 8 weeks before national championships qualifying for European championships. This follow-up period was divided to following microcycles: preparatory general, intensified training, preparatory specific, precompetition (tapering), and competition periods. RR-intervals were recorded every morning in supine (8 min) and orthostatic (6 min) positions with beat-bybeat heart monitors. Breathing was paced to 12 breaths/min. HRV was analyzed from the last 5-min period of both positions with FFT and autoregressive (AR) spectral power analysis. TRIMPs of every training session were calculated to estimate training. Results are presented as averages of each period and expressed in relative changes. RESULTS: Training load increased during the intensified training period (+86%, p=0.01) and progressively decreased during the precompetition and competition. HF spectral power during supine rest increased during intensified training (+38%, P=0.03) but recovered to baseline thereafter and stayed near baseline levels during tapering and competition periods. LF/HF ratio during supine rest progressively increased from preparatory general to tapering (+58%, P=0.02) and competition periods (+66%, P=0.01). CONCLUSION: The present findings are different from previous literature of HRV in endurance athletes. Intensive training has been reported to decrease HRV acutely and a rebound was observed after a relative resting period. In this study, increase of HRV seemed to be related to positive coping with increased training stress of elite swimmers. Interpretation of LF/HF ratio has been questionable, but it has been used as an indicator of the balance of autonomic nervous system. Therefore, these findings suggest that the sympathetic activity of elite swimmers may increase during rest as an anticipatory effect of competition period.